The tRNA Primer Activation Signal in the Human Immunodeficiency Virus Type 1 Genome Is Important for Initiation and Processive Elongation of Reverse Transcription - Beerens, Nancy (American Society for Microbiology, 2002)
Human immunodeficiency virus type 1 (HIV-1) reverse transcription is primed by the cellular tRNA(3)(Lys) molecule, which binds, with its 3"-terminal 18 nucleotides (nt), to a complementary sequence in the viral genome, the primer-binding site (PBS). Besides PBS-anti-PBS pairing, additional interactions between viral RNA sequences and the tRNA primer are thought to regulate the process of reverse transcription. We previously identified a novel 8-nt sequence motif in the U5 region of the HIV-1 RNA genome that is critical for tRNA(3)(Lys)-mediated initiation of reverse transcription in vitro. This motif activates initiation from the natural tRNA(3)(Lys) primer but is not involved in tRNA placement and was therefore termed primer activation signal (PAS). It was proposed that the PAS interacts with the anti-PAS motif in the TΨC arm of tRNA(3)(Lys). In this study, we analyzed several PAS-mutated viruses and performed reverse transcription assays with virion-extracted RNA-tRNA complexes. Mutation of the PAS reduced the efficiency of tRNA-primed reverse transcription. In contrast, mutations in the opposing leader sequence that trigger release of the PAS from base pairing stimulated reverse transcription. These results are similar to the reverse transcription effects observed in vitro. We also selected revertant viruses that partially overcome the reverse transcription defect of the PAS deletion mutant. Remarkably, all revertants acquired a single nucleotide substitution that does not restore the PAS sequence but that stimulates elongation of reverse transcription. These combined results indicate that the additional PAS-anti-PAS interaction is needed to assemble an initiation-competent and processive reverse transcription complex.